Problem-based learning dalam pembelajaran sastra anak untuk mengembangkan divergent thinking skills dalam penyusunan rancangan bahan ajar pada mahasiswa calon guru - Ardini, Anandayu Suri (Refleksi Pembelajaran Inovatif, 2025)
Problem-Based Learning (PBL) in enhancing students’ divergent thinking skills in the Children’s Literature course at the English Language Education Department, Universitas Islam Indonesia. Thirty-three students enrolled in the course participated in the study using a convenience sampling technique. A quantitative design with a one-group pretest-posttest model was employed. The instrument used was the Divergent Thinking Self-Assessment Scale developed by Sternberg (1997), adapted from 25 to 21 items. Students attended 14 class meetings consisting of four PBL cycles, each focusing on different children’s literature texts (The Book with No Pictures, Angryman, Cinderella, and I Like Your Way). Descriptive analysis revealed an increase in mean scores from the pretest (M = 2.71, SD = 0.31) to the posttest (M = 2.96, SD = 0.21). A paired sample t-test indicated a statistically significant difference (t(65) = 23.42, p < .001), with a mean difference of 1.37 (SD = 0.46). These findings demonstrate that PBL significantly improved students’ divergent thinking skills. Pedagogically, the results highlight the importance of integrating children’s literature and problem-based approaches to foster creativity, critical thinking, and prospective teachers’ ability to design contextual and inclusive teaching materials. Future studies are recommended to involve control groups and more diverse participants to explore the impact of PBL more comprehensively.